ANALISIS KEMAMPUAN NUMERASI SISWA DALAM MENGERJAKAN MATERI PECAHAN DI TINGKAT SEKOLAH DASAR - Ardila, Ivo; Armanto, Dian; Yus, Anita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students' numeracy skills in fractions. The study used a quantitative approach with descriptive methods. The subjects were 20 fourth-grade students at SD Negeri 106205 Pasar Baru who were selected using a purposive sampling technique. The research instrument was a test in the form of six essay numeracy questions, which covered three cognitive processes of numeracy: understanding, application, and reasoning. Before being used, the instrument was first tested for validity, reliability, difficulty level, and discriminatory power of the questions. The trial resulted in all questions being categorized as valid, having very high reliability, moderate difficulty level, and having good discriminatory power. The results showed that students' numeracy abilities were most dominant in the application category, with a percentage of 87.5%, followed by understanding at 47.5% and reasoning at 15%. Thus, it was obtained that fourth-grade students at SD Negeri 106205 Pasar Baru were more able to apply the concept of fractions in routine situations, but still had difficulty in understanding the concept in depth and reasoning in numeracy. Common mistakes students make when solving numeracy problems include rushing to determine the answer, not understanding the question's intent, and not following the steps correctly. Keywords: Numeracy Skills, Fractions, Elementary School.